Partial pedicle subtraction osteotomy (PPSO): A modification for PSO in treatment of sagittal deformities. - Mohamed wafa (Egyptian Spine Association, 2012)
Background data: Pedicle subtraction osteotomy is used for treatment of sagittal deformities. It has the advantages of being accomplished completely through a posterior approach. Neurological deficits that accompany the procedure are believed to be the result of a combination of subluxation, residual dorsal impingement, and dural buckling. Purpose: To introduce a new modification of the traditional pedicle subtraction osteotomy, in which we perform partial pedicle osteotomy; preserving the inferior third of the pedicle. This allows more smooth correction of the deformity, minimizes the injury or irritation of the nerve root below this pedicle, and decreases the incidence of subluxation and dorsal impingement. Since the correction occurs with theoretically smaller wedges, better closure and union of the osteotomy site is expected. Study design: Our retrospective study included 33 patients with sagittal plan deformity (16 cases of ankylosing spondylitis, 8 cases of old fractures, 5 cases of congenital kyphosis and 4 cases of postlaminectomy kyphosis after cord tumour resection). Methods: All patients were treated by our modifications of the pedicle subtraction osteotomy technique. Radiographic analysis included assessment of kyphosis by regional Cobb angle, and the CV7 sagittal plumb line in pre and post plain radiographs. Clinically, the patients are assessed by the Oswestry functional score. Results: Our series included 23 male and 10 females. The age was of a mean 42.3 years. The vertical plumb line distance from the first sacral segment improved to 3.4 cm compared to a mean of 9.3 preoperatively. The degree of correction for single osteotomy was of a mean of 22.4°. The intervertebral foramen below the osteotomised pedicle showed unchanged vertical dimension after the osteotomy. The complications included 4 cases of dural tears, 1 case of massive bleeding (2500 ml), 3 cases of superficial wound infection, and 1 case developed transient postoperative paraparesis. There was no single case of root injury. The follow-up of the patients was of mean 27.4 months. At the end of follow up, radiologically, there was a loss of correction of mean of 2 degrees with no case of pseudoarthrosis or metal failure. According to Oswestry disability score, 88% of patients were able to return to their normal to moderate daily activities with good self image and overall satisfaction. Conclusion: Although our new technique is technically demanding, it has lower rate of neurological complication with better chances of union than the traditional osteotomy.